1970
DOI: 10.1071/ar9700033
|View full text |Cite
|
Sign up to set email alerts
|

The comparative rates of phosphate absorption by eight annual pasture species

Abstract: Phosphate flux into roots from soil increased with increase in applied phosphate in eight annual pasture species, except in lupins at higher levels of application, where toxicity was pronounced. The rate of uptake decreased with time, the decrease being least in the clovers. The relationship between rate of uptake and level of applied phosphate was sigmoid for the legumes, less so for erodium and cape-weed, and non-sigmoid for the grasses. Marked differences among species were found in the distribution of abso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

1971
1971
1995
1995

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 0 publications
2
9
0
Order By: Relevance
“…They also concluded that L. eosentinii was more tolerant of low soil phosphate than other lupin species cultivated in Western Australia (L. cosentinii > L. luteus > L. angustifolius = L. albus). Similar findings were reported by Gladstones et al (1964) and by Keay, Biddiscombe and Ozanne (1970) who demonstrated L. cosentinii's strong ability to take up soil phosphate when compared with a range of non-lupin species.…”
Section: Introductionsupporting
confidence: 88%
“…They also concluded that L. eosentinii was more tolerant of low soil phosphate than other lupin species cultivated in Western Australia (L. cosentinii > L. luteus > L. angustifolius = L. albus). Similar findings were reported by Gladstones et al (1964) and by Keay, Biddiscombe and Ozanne (1970) who demonstrated L. cosentinii's strong ability to take up soil phosphate when compared with a range of non-lupin species.…”
Section: Introductionsupporting
confidence: 88%
“…It increased with supply, even when the yield response was saturated and P was being used with less efficiency. Similar decreases in the efficiency of P use as the supply increased have been noted by other workers (Keay et al 1970;White 1972;Awerbuch 1975;Christie & Moorby 1975).…”
Section: Discussionsupporting
confidence: 59%
“…In so-called inefficient strains there was a high level of mobility of these elements, possibly to a point where normal metabolic function was restricted. Other accounts of P partitioning between roots and shoots involve interspecific comparisons (Specht & Groves 1966;Rorison 1968;Biddiscombe et al 1969;Keay et al 1970;Barrow 1975;Temple-Smith & Menary 1977;Safaya et al 1979;Caradus 1980), and all but one show the reverse to the results of Gabelman (1976). The exception is Scabiosa columbaria, which has the ability to absorb P in excess of immediate requirements, resulting in high % P levels in its roots (Rorison 1968).…”
Section: P Partitioningmentioning
confidence: 91%